Perioperative blood pressure variability as a risk factor for postoperative delirium in the patients receiving cardiac surgery - Xiao Shen; Hong Tao; Wenxiu Chen; Jiakui Sun; Renhua Jin; Wenhao Zhang; Liang Hong; Cui Zhang (BMC Anesthesiology, 2024)
Abstract Background Delirium is one of the most common neurological complications after cardiac surgery. The purpose of our study was to assess the relationship between perioperative blood pressure variability (BPV) and postoperative delirium (POD) in the patients undergoing cardiac surgery. Methods Adult patients received cardiac surgery and stayed in Cardiovascular Intensive Care Unit (ICU) for more than 24 h after surgery during the study period between June 2019 and December 2022 were included in this study. Baseline characteristics, perioperative hemodynamic variables and postoperative laboratory results of the cardiac patients were collected and analyzed. Perioperative BPV was quantified by calculating the standard deviation (SD) and average real variability (ARV) of blood pressure. Assessment of delirium was based on the mental status of the patients and CAM-positive. The relationship between perioperative BPV and POD was analyzed by LASSO and logistic regression using R (R package, 4.3.2). Results The incidence of POD was 15.0% (324/2164) in the patients receiving cardiac surgery, and the average day for POD occurred at day 3 after surgery. Patients with POD had statistically lower levels of intraoperative mean blood pressure (P = 0.015) and blood pressure ARV (P < 0.001) as well as mean blood pressure at 24 h postoperatively (P = 0.003) when compared to those without. Whereas, ARV for systolic blood pressure (8.64 vs. 7.91 mmHg, P < 0.001), diastolic blood pressure (4.00 vs. 3.77 mmHg, P = 0.014) and mean blood pressure (5.23 vs. 4.94 mmHg, P = 0.001) at 24 h postoperatively was significantly higher in the patients with POD than those without. LASSO regression and further logistic regression revealed that intraoperative blood pressure ARV (OR:0.92, P < 0.001), mean central venous pressure (OR:1.05, P = 0.048) and ARV of systolic blood pressure (OR:1.17, P = 0.002) at 24 h postoperatively were independent risk factors for POD. Conclusions Perioperative ARV, especially postoperative high ARV exposure, was associated with POD in the patients receiving cardiac surgery. Maintaining a relatively stable blood pressure after cardiac surgery might be beneficial to avoid POD in those patients.